Can a virtual reality exposure therapy app improve symptoms of Emetophobia? A single-subject Experimental design study - Wallace, Rory; Lacey, Cameron; Sargisson, Rebecca J. (Journal of behavior therapy and experimental psychiatry, 2025)
Emetophobia (fear of vomiting) is an understudied disorder that affects .2 % of people, with extreme (non-phobic) fear affecting up to 8 % of people. The most effective treatment for specific phobias is exposure therapy, and virtual reality exposure therapy (VRET), has become a viable treatment alternative to traditional in-vivo or imaginal exposure therapy. However, using VRET to treat emetophobia has not yet been explored. We used a within-subjects, multiple-baseline-across-participants design with six participants to evaluate the emetophobia programme of oVRcome; a low-cost, Aotearoa New Zealand-based VRET app. After using the oVRcome VRET app, we saw visible improvements in self-reported phobia symptoms for four of the six participants (P2, P4, P5, and P6). For half the participants (P4, P5, and P6), the reported decreases were large, with two participants scoring below the threshold for a likely phobia diagnosis. The emetophobia programme of the oVRcome VRET app may be effective at reducing emetophobia severity, and our results support research showing eHealth apps can be a low-cost and effective treatment for a range of psychological issues. [Display omitted] •Emetophobia, the fear of vomiting, affects many people.•Low-cost virtual reality apps could reduce symptoms of emetophobia.•We used a multiple-baseline-across-participants, single-subject design.•We saw improvements in self-reported phobia symptoms for three of six participants.•Virtual reality eHealth apps can be a low-cost and effective treatment for phobias.